Efficacy and validity of automated quantitative chemiluminescent enzyme immunoassay for SARS-CoV-2 antigen test from saliva specimen in the diagnosis of COVID-19. Issue 7 (July 2021) - Asai, Nobuhiro; Sakanashi, Daisuke; Ohashi, Wataru; Nakamura, Akiko; Kawamoto, Yuzuka; Miyazaki, Narimi; Ohno, Tomoko; Yamada, Atsuko; Chida, Sumie; Shibata, Yuichi; Kato, Hideo; Shiota, Arufumi; et al.
Abstract: Introduction: The pandemic of a novel coronavirus disease 2019 (COVID-19) caused by a severe acute respiratory coronavirus 2 (SARS-CoV-2) infection has been problematic worldwide. A new SARS-CoV-2 antigen test (LUMIPULSE Ⓡ ) was licensed and widely used in Japan since May 2020. We conducted this study intending to whether the automated quantitative CLEIA antigen test using a saliva sample is effective and valid for the diagnosis of COVID-19. Patients and methods: We analyzed and compared the diagnostic accuracy of both the automated quantitative CLEIA antigen test and real-time RT-PCR (rRT-PCR) using a saliva sample from individuals suspected as having COVID-19. Results: A total of 305 samples were collected and tested in Aichi Medical University Hospital and affiliated facilities from December 2020 until January 2021 at our institute. Using reverse-transcription PCR as a reference, the AUROC of the automated quantitative CLEIA antigen test was 0.903 (95% confidential interval 0.845–0.962, p  < 0.001). The appropriate cut-off antigen level was 4.0 pg/mL and had a sensitivity of 77.8%, a specificity of 99.6%, a positive predictive value of 98%, and a negative predictive value of 94.5%. On the other hand, the diagnostic accuracy of the antigen test decreased among patients among patients with COVID-19 with threshold cycle (Ct-value)≥27, which shows the AUROC was 0.795 (95%CI 0.687–0.907, p  < 0.001). Conclusion: While the automated quantitative CLEIA antigen test from saliva specimen could be one of the most useful diagnostic tests for the diagnosis of COVID-19 in general practice, clinicians should know the limitations of the antigen test.